DEVELOPING READING MATERIAL IN THE FORM OF SHORT STORY BASED ON CENTRAL KALIMANTAN CULTURE (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This research aims to develop reading materials in the form of short stories based on Central Kalimantan culture. Reading materials for university level in the form of local content are still limited. In fact, Dayak culture can be an interesting alternative reading material besides providing academic texts to students. Based on the needs analysis, it is known that at the English Education Study Program of Universitas Palangka Raya, there is a need for reading materials that are able to improve reading skills while containing relevant texts with text difficulty levels that are appropriate for student levels. Further, the reading materials should be in accordance with student interests and needs, contain effective learning strategies, and integrate culture or local content. This research applies Developmental Research in accordance with the ADDIE stages (Analysis, Design, Development, Implementation, and Evaluation). Based on the Evaluation, the developed reading materials are in the form of short stories that contain Central Kalimantan cultural aspects embedded in activities, name of people, name of places, and name of food. The reading materials also contain exercises that demand students' skills in reading comprehension.
Keywords: reading comprehension; material development; Central Kalimantan culture